Spray-Deposited Anisotropic Assemblies of Plasmonic Nanowires for Direction-Sensitive Strain Measurement - Muller, Jean; Kumar, Charchit; Ghosh, Anik Kumar; Gupta, Vaibhav; Tschopp, Michel; Le Houerou, Vincent; Fery, Andreas; Decher, Gero; Pauly, Matthias; Felix, Olivier (ACS Applied Materials and Interfaces, 2022)
The development of nanoscale composites with hierarchical architecture and complex anisotropies enables the fabrication of new classes of devices. Stretchable strain sensors have been developed in the past for applications in various fields such as wearable electronics and soft robotics, yet the sensing capacities of most of these sensors are independent of the direction of deformation. In the present work, we report on the preparation of a direction-sensitive strain sensor using the anisotropic optical properties of a monolayer of oriented plasmonic 1D nano-objects. Grazing incidence spraying (GIS) is used for depositing a monolayer of in-plane aligned silver nanowires with a controlled density on a deformable and transparent substrate. Using the selective excitation of transverse and longitudinal localized plasmon resonance modes of silver nanowires by polarized UV-visible-NIR spectroscopy, we show that the macroscopic anisotropic properties of the monolayer upon stretching are highly dependent on the stretching direction and light polarization. Measuring the polarized optical properties of the anisotropic thin films upon stretching thus allow for retrieving both the local strain and the direction of the deformation using a simple model.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anisotropic optical properties; direction-sensitive strain sensor; oriented silver nanowire monolayer; polarized spectroscopy; spray coating